An international study of the use of pandemic vaccines during the 2009-10 influenza A(H1N1) pandemic: a qualitative methodological study - Pinder, Leila (2017)
Background: The 2009-10 influenza A(H1N1) pandemic was the first pandemic influenza of the twenty-first century and presented the first major opportunity for the use of influenza vaccines en-masse during a pandemic scenario. National anticipatory policies of pandemic influenza vaccine preparedness were implemented, and vaccine guarantee agreements were activated. Large quantities of vaccines were purchased and made available to identified citizens over the course of the pandemic. The use of pandemic influenza vaccines has been examined in this research.